Diagnosis of Genus Helicobacter through a hemi-nested PCR assay o - Heping Qin; Guodu Tang; Ping Yi; Xinyi Pan; Huali Huang; Renjie Chang; Zhe Shi; Muhammad Aqeel Ashraf (Elsevier, 2016)
The present study aimed to establish a genus-specific PCR-based assay to detect helicobacters using 16S rRNA gene as the target template. We designed the hemi-nested primers based on sequences of 16S rRNA gene of 34 types of Helicobacter species. The inclusivity, sensitivity, and specificity of the PCR assay using these primers were examined in three different models, comprising feces simulated samples, BLAB/c mice infection model and clinic patients samples. The detection sensitivity of Helicobacter pylori, Helicobacter hepaticus and Helicobacter bilis strains from feces simulated samples was all 102 CFU/ml. We successfully detected H. hepaticus and H. bilis in the liver, cecum and feces of experimentally infected mice. H. pylori was successfully detected in the feces samples from 3 patients infected with H. pylori while not in the feces samples from 3 healthy human. However, the C97/C05-C97/C98 PCR assay detected H. pylori in the 2 positive samples. Due to the PCR assay's excellent inclusivity, high sensitivity and specificity it may be used to detect the presence of Helicobacters.